Blockade of Endothelin-1 Receptor Type B Ameliorates Glucose Intolerance and Insulin Resistance in a Mouse Model of Obstructive Sleep Apnea - Polak, Jan; Punjabi, Naresh M.; Shimoda, Larissa A. (Frontiers in Endocrinology, 2018)
Obstructive sleep apnea (OSA) is associated with insulin resistance (IR) and glucose intolerance. Elevated endothelin-1 (ET-1) levels have been observed in OSA patients and in mice exposed to intermittent hypoxia (IH). We examined whether pharmacological blockade of type A and type B ET-1 receptors (ETA and ETB) would ameliorate glucose intolerance and IR in mice exposed to IH. Subcutaneously implanted pumps delivered BQ-123 (ETA antagonist; 200 nmol/kg/day), BQ-788 (ETB antagonist; 200 nmol/kg/day) or vehicle (saline or propyleneglycol [PG]) for 14 days in C57BL6/J mice (10/group). During treatment, mice were exposed to IH (decreasing the FiO2 from 20.9% to 6%, 60/h) or intermittent air (IA). After IH or IA exposure, insulin (0.5 IU/kg) or glucose (1 mg/kg) was injected intraperitoneally and plasma glucose determined after injection and area under glucose curve (AUC) was calculated. Fourteen-day IH increased fasting glucose levels (122 ± 7 vs. 157 ± 8 mg/dL, PG: 118 ± 6 vs. 139 ± 8; both p < 0.05) and impaired glucose tolerance (AUCglucose: 19,249 ± 1105 vs. 29,124 ± 1444, PG AUCglucose: 18,066 ± 947 vs. 25,135 ± 797; both p < 0.05) in vehicle-treated animals. IH-induced impairments in glucose tolerance were partially ameliorated with BQ-788 treatment (AUCglucose: 21,969 ± 662; p < 0.05). Fourteen-day IH also induced IR (AUCglucose: 7185 ± 401 vs. 8699 ± 401; p < 0.05). Treatment with BQ-788 decreased IR under IA (AUCglucose: 5281 ± 401, p < 0.05) and reduced worsening of IR with IH (AUCglucose: 7302 ± 401, p < 0.05). There was no effect of BQ-123 on IH-induced impairments in glucose tolerance or IR. Our results suggest that ET-1 plays a role in IH-induced impairments in glucose homeostasis.